2011
DOI: 10.1021/jp204128k
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA Dewar Photoproduct to (6-4) Photoproduct in (6-4) Photolyase

Abstract: Dewar photoproduct (Dewar PP) is the valence isomer of (6-4) photoproduct ((6-4)PP) in photodamaged DNA. Compared to the extensive studied CPD photoproducts, the underlying repair mechanisms for the (6-4)PP, and especially for the Dewar PP, are not well-established to date. In this paper, the repair mechanism of DNA Dewar photoproduct T(dew)C in (6-4) photolyase was elucidated using hybrid density functional theory. Our results showed that, during the repair process, the T(dew)C has to isomerize to T(6-4)C pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Photolyases reverting 64PPs have been described in a series of eukaryotic cells in addition to those handling CPDs (Essen and Klar, ; Sancar, ). Interestingly, biochemical studies showed that these 64PPs photolyases may also repair DEWs but with little efficiency compared with 64PPs (Yamamoto et al ., ; Glas et al ., ; ; Ai et al ., ; ; Fingerhut et al ., ). In addition, TT DEW was found to be reluctant to photoreversion.…”
Section: Discussionmentioning
confidence: 99%
“…Photolyases reverting 64PPs have been described in a series of eukaryotic cells in addition to those handling CPDs (Essen and Klar, ; Sancar, ). Interestingly, biochemical studies showed that these 64PPs photolyases may also repair DEWs but with little efficiency compared with 64PPs (Yamamoto et al ., ; Glas et al ., ; ; Ai et al ., ; ; Fingerhut et al ., ). In addition, TT DEW was found to be reluctant to photoreversion.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the reaction mechanism of repair of the T(Dew)C lesion by (6‐4) PL, theoretical and experimental studies agree that that the first step is reversion of the Dewar PP to a (6‐4) PP upon electron injection by photoexcited FADH − . The (6‐4) PP would subsequently be repaired as discussed above.…”
Section: Repair Of Dewar Photoproductsmentioning
confidence: 85%
“…With respect to the inability of (6‐4) PL to repair the T(Dew)T lesion , this cannot be attributed to poor substrate binding, as a high affinity for T(Dew)T‐containing substrates has been demonstrated . Rather, reversion of the T(Dew)T to the T(6‐4)T lesion appears to be inhibited, either by an unfavorable electron transfer from photoexcited FADH − to T(Dew)T or by a higher activation barrier for the splitting of the N3′‐C6′ bond in the anion radical of the T(Dew)T lesion (compared to T(Dew)C) .…”
Section: Repair Of Dewar Photoproductsmentioning
confidence: 99%
“…The fact that plant cells can effectively repair selected types of UV-induced DNA lesions via photoreactivation has been well documented. According to our knowledge, the activity of this repair system in plants is limited to the repair of CPDs, 6-4 PPs and Dewar photoproducts only [14][15][16]. Photoreactivation is performed by photolyases which use UV-A/blue light energy to simply reverse pyrimidine dimers formed under UV.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%